Estimation of Physalin in callus, closed continuous and batch cultures of Physalis angulata L. - AL-Mahdawe, Muthana Muhamad; Ahmad, Talfan Anad; Nadir, Dhuha Sabah (Journal of Kerbala for Agricultural Sciences, 2018)
This experiment was conducted steroids from leaves of Physalis angulata L. at the flowering stage and from callus derived from hypocotyle stems and from the nutrient medium for closed continuous culture at age of 7, 14, 21 days and from harvested cells of batch cultures. Using High Performance Liquid Chromatography Technique (HPLC), the data showed that these cultures were containing both Physalin A and B when compared with the standard samples. Physalin A and B constrations in leaves were 24.36 and 34.18 µg.ml-1 respectively and in callus culture at the age of 30 days the constrations of Physalin A and B were 287.28 and 238.47 µg.ml-1 respectively, while the samples of liquid medium of closed continuous cultures at the age 7, 14 and 21 days showed that Physalin A concetrations were 97.67, 137.88 and 85.79 µg.ml-1 respectively, whereas Physalin B constrations for the same age groups reached 103.36, 194.19 and 40.96 µg.ml-1 respectively. However, the lowest concetrations of Physalin A and B of the harvested cells from the batch cultures were 10.11 and 15.59 µg.ml-1 respectively. These data indicate that it is possible to produce Physalin A and B by using tissue cultures as a constant and continuous source for the production of secondary metabolites and considering the tissue cultures as an alternative source for the field plants.